Autophagy inhibition overcomes sorafenib resistance in S45F‐mutated desmoid tumors. Issue 15 (12th April 2019) - Braggio, Danielle; Koller, David; Jin, Feng; Siva, Nanda; Zewdu, Abeba; Lopez, Gonzalo; Batte, Kara; Casadei, Lucia; Welliver, Meng; Strohecker, Anne M.; Lev, Dina; Pollock, Raphael E.
Abstract : Background: Desmoid tumors (DTs) are rare and understudied fibroblastic lesions that are frequently recurrent and locally invasive. DT patients often experience chronic pain, organ dysfunction, decrease in quality of life, and even death. Methods: Sorafenib has emerged as a promising therapeutic strategy, which has led to the first randomized phase 3 clinical trial devoted to DTs. Concurrently, we conducted a comprehensive analysis of sorafenib efficacy in a large panel of desmoid cell strains to probe for response mechanism. Results: We found distinctive groups of higher‐ and lower‐responder cells. Clustering the lower‐responder group, we observed that CTNNB1 mutation was determinant of outcome. Our results revealed that a lower dose of sorafenib was able to inhibit cell viability, migration, and invasion of wild‐type and T41A‐mutated DTs. Apoptosis induction was observed in those cells after treatment with sorafenib. On the other hand, the lower dose of sorafenib was not able to inhibit cell viability, migration, or invasion or to induce apoptosis in the S45F‐mutated DTs. The investigation of autophagy showed the dependency of S45F‐mutated DTs on this pathway as a part of cell survival mechanism. Significantly, when autophagy was inhibited genetically or pharmacologically in the S45F mutant cell strains, sensitivity to sorafenib was restored. Conclusions: Our findings suggest that the response to sorafenib differs when comparing S45F‐mutated DTs and T41A‐mutated or wild‐type DTs. Furthermore, the combination of hydroxychloroquine and sorafenib enhances the antiproliferative and proapoptotic effects in S45F‐mutated DT cells, suggesting that profiling β‐catenin status could guide clinical management of desmoid patients who are considering sorafenib treatment. Abstract : Sorafenib treatment is more effective in wild‐type and T41A‐mutated DT cell strains. The resistance observed in S45F‐mutated cells is driven by elevated basal autophagy and could be reversed by autophagy inhibition.